Answer:
z^11
Step-by-step explanation:
since both terms have "z" and the operation is multiplication, you <u>add</u><u> </u><u>the exponents</u><u> </u>together
Answer:16
Step-by-step explanation:
8^(4/3)=(cube root of 8)^4=2^4=2×2×2×2=16
Answer:
The distributive property is not properly applied to the second polynomial.
Step-by-step explanation:
For whatever reason, it is a common mistake to say that ...
-(a +b +c) = -a +b +c . . . . WRONG!
Rather, it should be ...
-(a +b +c) = -a -b -c . . . . CORRECT
Answer:
here
Step-by-step explanation:
2b^2. This is because you have a positive a^2 and a negative so they cross it one another so it just leaves the b’s.